2020
DOI: 10.1007/s10815-020-01877-5
|View full text |Cite
|
Sign up to set email alerts
|

Microgravity effects on frozen human sperm samples

Abstract: This work was approved by the Ethics Committee and Review Board of the Center Consent to participate: Study participants were informed of the procedure and gave their consent to participate by signing the informed consent. Availability of data and material: All relevant data are within the paper Code availability: Not applicable Authors' contributions: M. Boada and A. Perez-Poch conceived the study; D.V. González conducted the parabolic flights; M. Ballester and S. García-Monclús performed the seminal tests; S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Boada et al reported that the exposure of healthy donors to parabolic flight did not affect sperm count, as no significant changes between the experimental and control groups (39.01 ± 32.02 × 10 6 /ml versus 39.29 ± 36.53 × 10 6 /ml) was observed. This result reinforces the previous hypothesis that sperm is protected against microgravity by freezing them in comparison to the fresh ones ( Boada et al, 2020 ). Additionally, Kumar et al showed that after exposure to occupational ionizing radiation, the total sperm count was not affected, as there was no statistically significant difference between the exposed and non-exposed men (64.16 ± 4.40 × 10 6 /ml versus 68.44 ± 5.98 × 10 6 /ml) ( Kumar et al, 2013 ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Boada et al reported that the exposure of healthy donors to parabolic flight did not affect sperm count, as no significant changes between the experimental and control groups (39.01 ± 32.02 × 10 6 /ml versus 39.29 ± 36.53 × 10 6 /ml) was observed. This result reinforces the previous hypothesis that sperm is protected against microgravity by freezing them in comparison to the fresh ones ( Boada et al, 2020 ). Additionally, Kumar et al showed that after exposure to occupational ionizing radiation, the total sperm count was not affected, as there was no statistically significant difference between the exposed and non-exposed men (64.16 ± 4.40 × 10 6 /ml versus 68.44 ± 5.98 × 10 6 /ml) ( Kumar et al, 2013 ).…”
Section: Discussionsupporting
confidence: 92%
“…Samples exposed to microgravity had a mean of 13.33 ± 5.12% sperm fragmentation, while control samples had a mean of 13.88 ± 6.14%. The mean percentage of SDF was similar in both groups ( Boada et al, 2020 ).…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations